Prevalence of Diabetic Retinopathy among Diabetic Patients Attending a Tertiary Care Hospital in Nepal: An Observational Study - Chhetri, Sundip Dware; Kunwar, Meena; Thapa, Ashish; Shrestha, Apurba; Sah, Dayanand Prasad; Lamichhane, Kriti (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: The global rise of type II diabetes has increased the number of individuals at risk for retinal complications such as diabetic retinopathy, a leading cause of vision impairment. In Nepal, a significant number of patients are diagnosed with diabetic retinopathy only at advanced stages. Diabetic retinopathy is commonly linked to longer duration of diabetes, uncontrolled blood sugar, and elevated blood pressure. Timely detection and management are crucial to prevent irreversible vision loss. This study aimed to assess the prevalence of diabetic retinopathy among diabetic patients visiting a tertiary care hospital. Methods: A hospital-based observational study was conducted between September 1, 2025 and December 26, 2025, at a tertiary care hospital. Ethical approval was obtained from the Institutional Review Committee (Reference number: NAPFH-041/2025). Detailed demographic, clinical, and ocular examination findings were recorded. A purposive sampling technique was used. Data were analyzed with Microsoft Excel and Statistical Package for the Social Sciences version 17. Results: Out of 195 diabetic patients, the mean age was 54.7±10.17 years. The overall prevalence of diabetic retinopathy was 18 (9.23%), of which 17 (8.71%) had non-proliferative diabetic retinopathy, and 1 (0.51%) had proliferative diabetic retinopathy. Diabetic macular edema was present in 1 (0.51%) of cases. Diabetic retinopathy was more common in patients with longer duration of diabetes and associated complications, including nephropathy. Conclusions: Diabetic retinopathy continues to be a major complication among patients with diabetes in Nepal, with many cases identified late due to inadequate prior eye screening. Regular monitoring and early treatment are vital to avoid vision-threatening consequences.